Factors associated with postnatal care utilisation in Rwanda: A secondary analysis of 2010 Demographic and Health Survey data - Rwabufigiri, Bernard N. (BMC Pregnancy Childbirth, 2016)
BACKGROUND: Postnatal care (PNC) in the first seven days is important for preventing morbidity and mortality in mothers and new-borns. Sub-Saharan African countries, which account for 62 % of maternal deaths globally, have made major efforts to increase PNC utilisation, but utilisation rates remains low even in countries like Rwanda where PNC services are universally available for free. This study identifies key socio-economic and demographic factors associated with PNC utilisation in Rwanda to inform improved PNC policies and programs. METHODS: This is a secondary analysis of the 2010 Demographic and Health Survey, a national multi-stage, cross-sectional survey. In bivariate analysis, we used chi-square tests to identify demographic and socio-economic factors associated with PNC utilisation at α = 0.1. Pearson’s R statistic (r > 0.5) was used to identify collinear covariates, and to choose which covariate was more strongly associated with PNC utilisation. Manual backward stepwise logistic regression was performed on the remaining covariates to identify key factors associated with PNC utilisation at α = 0.05. All analyses were performed in Stata 13 adjusting for sampling weights, clustering, and stratification. RESULTS: Of the 2,748 women with a live birth in the last two years who answered question about PNC utilisation, 353 (12.8 %) returned for PNC services within seven days after birth. Three factors were positively associated with PNC use: delivering at a health facility (OR: 2.97; 95 % CI: 2.28–3.87), being married but not involved with one’s own health care decision-making (OR: 1.69; 95 % CI: 1.17, 2.44) compared to being married and involved; and being in the second (OR: 1.46; 95 % CI: 1.01–2.09) or richest wealth quintile (OR: 2.04; 95 % CI: 1.27–3.29) compared to the poorest. Mother’s older age at delivery was negatively associated with PNC use (20–29 – OR: 0.51, 95 % CI: 0.29–0.87; 30–39 – OR: 0.47, 95 % CI: 0.27–0.83; 40–49 – OR: 0.32, 95 % CI: 0.16–0.64). CONCLUSIONS: Low PNC utilisation in Rwanda appears to be a universal problem though older age and poverty are further barriers to PNC utilisation. A recent change in the provision of BCG vaccination to new-borns might promote widespread PNC utilisation. We further recommend targeted campaigns to older mothers and poorest mothers, focusing on perceptions of health system quality, cultural beliefs, and pregnancy risks.